1973
DOI: 10.1007/bf02376344
|View full text |Cite
|
Sign up to set email alerts
|

Spillway with nappe aeration

Abstract: An increase in the height of spiUways of high dams leads to an intense increase in the cavitation action of the flow. Experimental investigations by many authors have shown that cavitation erosion occurs at a stream velocity greater than 12-15 m/sec and its intensity increases proportionally as the 5-7 power of the velocity. With an increase in spillway height, for example, from 50 to 100 m, the rate of cavitation erosion increases by a factor of 6-8. and with an increase to 150 m by a factor of more than 40. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1974
1974
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Peterka (1953) demonstrated that 2% of air concentration reduced significantly and 8% eliminated the damage caused by cavitation. Semenkov & Lentyaev (1973) suggested that the stronger the concrete, the less need for air concentration. According to the authors, considering a 40 MPa concrete, 3% of air concentration is needed to eliminate cavitation damage.…”
Section: Introductionmentioning
confidence: 99%
“…Peterka (1953) demonstrated that 2% of air concentration reduced significantly and 8% eliminated the damage caused by cavitation. Semenkov & Lentyaev (1973) suggested that the stronger the concrete, the less need for air concentration. According to the authors, considering a 40 MPa concrete, 3% of air concentration is needed to eliminate cavitation damage.…”
Section: Introductionmentioning
confidence: 99%
“…Note that for this investigation, the hydraulic and geometric characteristics of the standing and shock waves were not evaluated in any further detail, as these factors did not form part of the study objective. From the above results, it is observed that the bottom air concentrations downstream of chute aerator in the spillway model with no pier can be considered sufficient to protect the chute surface against cavitation damage, since the measured air concentrations during the present investigation are into the range of the amount of air needed for cavitation protection, proposed by previous researchers [10][11][12][13][14]. This is further reinforced by Kramer [71] statement, who corroborated that a small percentage of air distributed as small bubbles next to the spillway invert is sufficient to protect a concrete surface.…”
Section: Resultsmentioning
confidence: 52%
“…Rasmussen [11] developed a series of experiments and demonstrated that no cavitation damage occurred by adding a 0.8% to 1% of air by volume distributed as small bubbles. Semenkov and Lentiaev [12] investigated the cavitation damage experienced by concrete surfaces and found that an air concentration of at least 3% is needed to avoid damaging effects. Pylaev [13] corroborated that an air concentration of 3% is required for avoiding cavitation erosion.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, there is no reliable design guideline for the distance required between two aerators to produce sufficient bottom air concentration [5]. Based on prototype observations on Russian dams, Semenkovand Lantyaev [20] provided an average bottom air concentration decay of 0.40% to 0.80% per chute meter.…”
Section: Introductionmentioning
confidence: 99%